XIAP, the guardian angel - Holcik, Martin; Korneluk, Robert G. (Nature reviews. Molecular cell biology, 2001)
Controlling the activity of caspases is essential for the appropriate execution of cell death and the regulation of cell survival. One cellular inhibitor of apoptosis, XIAP, has emerged as a crucial regulator of caspases, and is itself subject to complex negative regulation.